The quality of life of family health professionals: a systematic review and meta-synthesis - Pedro Rogério Camargos Pennisi; Natalia Caroline Alves; Pietra Sanitá Michelin; Lívia Medeiros-Souza; Álex Moreira Herval; Luiz Renato Paranhos
ABSTRACT Objectives: to perform a systematic review and meta-synthesis of qualitative studies about the work-related quality of life of Family Health Strategy professionals. Methods: this systematic review was developed to answer the following PVO question: "Which factors (variables) are associated with the work-related quality of life (outcome) of Family Health Strategy professionals (population)?" The PubMed, Scopus, Embase, SciELO, Web of Science, LILACS, Science Direct, OpenThesis, OpenGrey, and OATD databases were selected. The meta-synthesis analyzed the main codes and secondary codes of all included studies. Results: the database search resulted in 1,744 reports; six were considered eligible for the meta-synthesis. Four factors were considered for the quality of work life: working conditions; work processes; interpersonal relationships; and personal aspects. Conclusions: although this study confirms the adequacy of aspects commonly related to the quality of work life, other factors are important in the case of FHS professionals, especially work context.